Allocation and sizing of DG using cuckoo search algorithm - Tan, W. S. (2012)
Recent years, penetration of distributed generation in the distribution system is one of the most attractive studies along with the creation of retail electricity markets and pressure place on countries to exploit the renewable resources. For exploiting the DG potential, the optimal allocation and sizing of DG are essential. In this paper, a novel Cuckoo Search algorithm is presented for optimal location and sizing of distributed generation on a radial distribution system. The objectives are to minimize the total real power losses and improve voltage stability within the system at the same time improve voltage profile within the voltage constrains. Cuckoo Search algorithm toolbox which coded in Matlab generates both optimal distributed generation site and size as outputs. Two case studies are carried out on 69 bus radial distribution systems and compare to the Standard Genetic Algorithm and Particle Swarm Optimization to verify the efficiency of the proposed methodology. The results show that Cuckoo Search algorithm outperforms other algorithms in terms of solution quality and standard deviation values.